2002
DOI: 10.1021/jo016180s
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Efficient Chemoselective Method for the Catalytic Deprotection of Acetals and Ketals Using Bismuth Triflate

Abstract: Bismuth triflate is a highly efficient catalyst (0.1-1 mol %) for the deprotection of acetals and ketals. The procedure is very facile and selective for acetals derived from ketones and conjugated aldehydes. tert-Butyldimethylsilyl ethers are stable to the reaction conditions. The highly catalytic nature of bismuth triflate and the use of a relatively nontoxic solvent system (THF/H(2)O) make this procedure particularly attractive for large-scale synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…It is noteworthy that the authors have utilised excess of alcohol (1 mL for the reaction performed on 1.5 mmol scale), which being a good solvent, may be responsible for the enhanced rates of the reaction. This observation of solvent dependency in Bi(III)-mediated reactions is in line with what has been observed in earlier investigations [44]. Further, the solvent dependent nature of the reaction made us curious about carrying out the reaction in the newer reaction media, viz.…”
Section: Screening Of Metal Nitratessupporting
confidence: 89%
See 1 more Smart Citation
“…It is noteworthy that the authors have utilised excess of alcohol (1 mL for the reaction performed on 1.5 mmol scale), which being a good solvent, may be responsible for the enhanced rates of the reaction. This observation of solvent dependency in Bi(III)-mediated reactions is in line with what has been observed in earlier investigations [44]. Further, the solvent dependent nature of the reaction made us curious about carrying out the reaction in the newer reaction media, viz.…”
Section: Screening Of Metal Nitratessupporting
confidence: 89%
“…Bismuth nitrate pentahydrate (BNP) possesses the optimum blend of all the above-said properties. The potential of BNP as a versatile and efficient catalyst for several reactions has already been explored [42][43][44][45][46][47][48]. Encouraged by the results obtained with BNP as a catalyst for Ferrier rearrangement, we planned a systematic study in which all the intricacies of the BNP-mediated reactions were probed.…”
Section: Screening Of Metal Nitratesmentioning
confidence: 99%
“…Scheme 44 In addition, Bi(OTf) 3 , 4H 2 O also proved to be an efficient catalyst for the cleavage of a variety of acetals and ketals derived from alkyl and aryl aldehydes and ketones using as little as 0.1 mol % of the catalyst (Scheme 45). [79] Moreover, it has been shown that a chemoselective deprotection could be realized since tetrahydropyranyl and tertbutyldimethylsilyl ethers were resistant to this deprotection method. Scheme 45 …”
Section: Formation and Cleavage Of Acetalsmentioning
confidence: 99%
“…The reaction in the presence of catalytic amount of trifluoromethane sulfonic acid as the catalyst in acetonitrile was also examined in order to understand which of the salt (bismuth salt) or the Bronsted acid (trifluoromethane sulfonic acid) has the key role in this reaction. We found that the reaction was proceeded by CF 3 SO 3 H to afford the corresponding product in less than 1 h. However, since the solvent of the reaction is aprotic in contrast to the solvent (H 2 O/THF) used by Mohan's group 36 it seems in this conditions the Lewis acid catalyses the reaction. In other words, under this circumstance the existence of equilibrium between Bi salts and their acids is doubtful.…”
Section: Resultsmentioning
confidence: 84%